Peran Gaya Hidup dalam Memediasi Pengaruh Pengetahuan dan Sikap Keuangan terhadap Perilaku Keuangan - Latifa, Nur; Santoso, Rahmat Agus (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
This study aims to examine the influence of financial knowledge and financial attitudes on financial behavior which is mediated by lifestyle. This research was conducted on postgraduate students in the North Coast region of East Java with a sample size of 176 respondents. The research method uses quantitative. The research results show that financial knowledge has no influence on financial behavior. Financial attitudes influence financial behavior variables. Financial knowledge has no effect on lifestyle. Financial attitudes influence lifestyle. Lifestyle influences financial behavior. This research shows that lifestyle cannot mediate financial knowledge on financial behavior, but lifestyle can mediate financial attitudes on financial behavior. There is novelty in lifestyle that can mediate financial attitudes towards financial behavior. An important implication of this research is the need for a more holistic approach in managing financial behavior, taking into account the interaction between knowledge, attitudes and lifestyle. In addition, these findings also highlight the importance of developing financial education strategies that not only focus on increasing knowledge, but also on forming positive financial attitudes and a deep understanding of the influence of lifestyle on financial decisions.